Overexpression of sesame polyketide synthase A leads to abnormal pollen development in Arabidopsis - Tianyu Li; Yuanxiao Yang; Hongyan Liu; Senouwa Segla Koffi Dossou; Fang Zhou; Ting Zhou; Yingzhong Zhao (BMC Plant Biology, 2022)
Abstract Background Sesame is a great reservoir of bioactive constituents and unique antioxidant components. It is widely used for its nutritional and medicinal value. The expanding demand for sesame seeds is putting pressure on sesame breeders to develop high-yielding varieties. A hybrid breeding strategy based on male sterility is one of the most effective ways to increase the crop yield. To date, little is known about the genes and mechanism underlying sesame male fertility. Therefore, studies are being conducted to identify and functionally characterize key candidate genes involved in sesame pollen development. Polyketide synthases (PKSs) are critical enzymes involved in the biosynthesis of sporopollenin, the primary component of pollen exine. Their in planta functions are being investigated for applications in crop breeding. Results In this study, we cloned the sesame POLYKETIDE SYNTHASE A (SiPKSA) and examined its function in male sterility. SiPKSA was specifically expressed in sesame flower buds, and its expression was significantly higher in sterile sesame anthers than in fertile anthers during the tetrad and microspore development stages. Furthermore, overexpression of SiPKSA in Arabidopsis caused male sterility in transgenic plants. Ultrastructural observation showed that the pollen grains of SiPKSA-overexpressing plants contained few cytoplasmic inclusions and exhibited an abnormal pollen wall structure, with a thicker exine layer compared to the wild type. In agreement with this, the expression of a set of sporopollenin biosynthesis-related genes and the contents of their fatty acids and phenolics were significantly altered in anthers of SiPKSA-overexpressing plants compared with wild type during anther development. Conclusion These findings highlighted that overexpression of SiPKSA in Arabidopsis might cause male sterility through defective pollen wall formation. Moreover, they suggested that SiPKSA modulates vibrant pollen development via sporopollenin biosynthesis, and a defect in its regulation may induce male sterility. Therefore, genetic manipulation of SiPKSA might promote hybrid breeding in sesame and other crop species.